Remittance trends in Myanmar: January - June 2024 - van Asselt, Joanna; Naing, Phyo Thandar (International Food Policy Research Institute, 2025)
Remittances have emerged as an important source of income for households in post-coup Myanmar. This paper utilizes data from the seventh and fourth rounds of the Myanmar Household Welfare Survey (MHWS) to analyze remittance trends between January and June 2024 with trends from July to December 2022. These two rounds are compared because they both contain detailed questions on remittances.